The Effect of Corporate Governance and Environmental Performance on the Disclosure of Carbon Emissions in Manufacturing Companies listed on the Indonesia Stock Exchange (IDX) - Syntia Sumarni; Linda Wahyu Marpaung (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2024)
This study aims to determine whether corporate governance and environmental performance have a significant effect on the disclosure of carbon emissions in manufacturing companies listed on the Indonesia stock exchange. This research uses quantitative methods. The research population uses data from 2018 to 2022 sourced from www.idx.co.id and the company's website with a total sample of 60 company reports. The sampling technique used purposive sampling. Data analysis and testing consists of descriptive statistics, classical assumption tests, multiple linear regression analysis, partial (T test) and simultaneous (F test) hypothesis testing, and the coefficient of determination test (R² test). Partial research results show that corporate governance has no effect and is not significant to the disclosure of carbon emissions. Environmental performance has a significant effect on disclosure of carbon emissions. Based on the results of simultaneous testing, it is known that the results of the F test show that corporate governance and environmental performance have a significant effect on disclosure of carbon emissions.